Varying strategies for processing “loose” argument structure in West Germanic languages - Renzel, Anne; De Vogelaer, Gunther; Bölte, Jens (Frontiers in Language Sciences, 2025)
Permissive subjects are non-agentive subjects combined with action verbs in the active form (e. g., “A few years ago a penny would buy you two or three pins”; “The tentsleeps four people”), hardly found in German compared to English. For this contrast, previous research offers an explanation related to processing constraints, proposing that distinct processing strategies account for varying efficiency of processing permissive subjects. The differences in processing strategies are said to be linked to typological properties, specifically word order. It is argued that if a language has SVO order (like English), permissive subjects should be better processed due to more routinized look ahead parsing strategies. In contrast, if a language is SOV (like German), parsers should be more used to look back parsing strategies, leading to difficulties in processing permissive subjects. The present study addresses the question how look ahead vs. look back parsing strategies for permissive subjects depend on features like SVO/SOV. Additionally to English and German, we investigate Dutch, as it is also SOV but seems to allow slightly more diverse roles in the grammatical subject than German. In order to demonstrate cross-linguistic differences in the processing of various types of permissive subjects, we conducted an experiment in which native speakers of English (n = 40), Dutch (n = 45), and German (n = 45) performed a self-paced reading task. The results reveal that German speakers experience greater difficulty processing permissive subjects, as evidenced by considerably slower reading times compared to English speakers. Reading times for Dutch speakers fall between those of English and German speakers. This pattern is not limited to documented permissive subjects, but extends beyond allegedly grammatical constructions (e.g., “The houselives four families”), which are also read faster in English and Dutch than in German. Therefore, our findings suggest fundamental differences in processing strategies for non-agentive subject-verb combinations between English and Dutch (look ahead) on the one hand and German (look back) on the other relating to other typological contrasts than word order influencing the processing of permissive subjects, most likely case.